Targeted metabolomic profiling reveals inflammation–associated longitudinal changes in plasma metabolites following on-pump coronary bypass surgery - Neu, Frieder; Wacker, Max; Schuchardt, Sven; Varghese, Sam; Awad, George; Waqas, Fakhar H.; Wippermann, Jens; Pessler, Frank; Veluswamy, Priya (Frontiers in Medicine, 2025)
AimsCardiac surgery leads to major post-operative changes in metabolism, but their exact nature and the underlying risk factors remains obscure. We aimed to characterize changes in plasma metabolites after coronary artery bypass grafting (CABG) to identify intra- and post-operative risk factors for global and specific alterations in plasma metabolites post-operatively.MethodsWe performed a targeted metabolomic screen on plasma samples from patients undergoing on-pump CABG for coronary artery disease (CAD), collected 1 day before and 1, 3, and 7 days after surgery. We assessed correlations with parameters of intra-operative course (cardiopulmonary bypass time and aortic cross-clamping time), intensive care unit (ICU) care, (length of ICU stay, duration of mechanical ventilation, duration of epinephrine/dobutamine or norepinephrine therapy), and systemic inflammation.ResultsOut of 1,019 detectable analytes, 970 passed the quality screen and were included in the analysis. With respect to d0, the greatest degree of change in metabolite populations occurred by d1, but substantial changes persisted through d7. Metabolites could be classified into those which were predominantly downregulated (e.g., triglycerides, bile acids, cholesterol esters, lysophosphatidylcholines, indoles and derivatives), up- or downregulated (e.g., phosphatidylinositol, phosphatidylethanolamines, phosphatidic acids, ceramides), or upregulated (free fatty acids, monoglycerides). Concentrations of food- and/or microbiota-derived metabolites (indole derivatives, trimethylamine N-oxide, trigonelline) were markedly reduced, particularly on d1 and d3. Changes in metabolite concentrations correlated most strongly with plasma C-reactive protein concentration (r = −0.67 to 0.59) and blood leukocyte count (−0.63 to 0.32) and less with intra-operative (−0.62 to 0.50) and ICU care (−0.52 to 0.38) parameters. Of note, neither C-reactive protein (CRP) nor leukocyte count correlated significantly with an intra-operative or ICU parameter.ConclusionsThese results reveal pronounced changes in plasma metabolite populations after CABG, which likely result from the combined effects of surgical and post-operative stress, systemic inflammation, reduced dietary intake, and possibly changes in gut microflora.